Chronic perchlorate exposure impairs stickleback reproductive behaviour and swimming performance - Bernhardt, Richard R. (2008)
We describe behavioural changes in two generations of threespine stickleback (Gasterosteus aculeatus) exposed to environmentally relevant concentrations of perchlorate. The first generation (G(0,2002)) was exposed as two-year-old adults to perchlorate in experimental groups ranging in concentration from less than the method detection limit (<1.1 ppb) to 18.6 ppm for up to 22 days during their courtship, spawning, egg guarding, and first five days of fry guarding. No differences were noted in the behaviour or reproductive output of these fish that were exposed as adults. However, perchlorate exposure throughout development caused widespread effects in the second generation (G(1,2003)), which was spawned and raised through sexual maturity in one of four nominal experimental groups (0, 30 and 100 ppm, and a ‘variable’ treatment that progressively increased from <1.1 ppb to approximately 60 ppm perchlorate). Dose-dependent effects were found during the G(1,2003)’s swimming and behavioural evaluations, including higher mortality rates among treated fish following stressful events. Perchlorate-exposed fish had higher failure rates during swimming trials and failed at lower flow rates than control fish. A number of treated fish exhibited seizures. Progressively fewer males completed benchmark metrics, such as nest building, spawning, nursery formation, or fry production, in a dose-dependent manner. Fewer males from higher treatments courted females, and those that did initiated courtship later and had a reduced behavioural repertoire compared to fish from lower treatments. The lowest observed adverse effect level (LOAEL) for swimming performance, reproductive behaviour, survivorship and recruitment was 30 ppm perchlorate (our lowest G(1,2003) treatment), and near complete inhibition of reproductive activity was noted among males raised in 100 ppm perchlorate. A small number of treated G(1,2003) females were isolated in aquaria, and some performed reproductive behaviour typical of males, such as biting, leading and zig-zagging in the presence of gravid females. These findings have profound implications for recruitment in wild fish populations exposed to perchlorate, and suggest that perchlorate may disrupt behaviour in other vertebrates as well.